Thermal conductivity of thin insulating films determined by tunnel magneto-Seebeck effect measurements and finite-element modeling. (10th May 2018) - Huebner, Torsten; Martens, Ulrike; Walowski, Jakob; Münzenberg, Markus; Thomas, Andy; Reiss, Günter; Kuschel, Timo
Abstract: In general, it is difficult to access the thermal conductivity of thin insulating films experimentally by electrical means. Here, we present a new approach utilizing the tunnel magneto-Seebeck effect (TMS) in combination with finite-element modeling (FEM). We detect the laser-induced TMS and the absolute thermovoltage of laser-heated magnetic tunnel junctions with 2.6 nm thin barriers of MgAl2 O4 (MAO) and MgO, respectively. A second measurement of the absolute thermovoltage after a dielectric breakdown of the barrier grants insight into the remaining thermovoltage of the stack. Thus, the pure TMS without any parasitic Nernst contributions from the leads can be identified. In combination with FEM via COMSOL, we are able to extract values for the thermal conductivity of MAO (0.7 W (K · m) −1 ) and MgO (5.8 W (K · m) −1 ), which are in very good agreement with theoretical predictions. Our method provides a new promising way to extract the experimentally challenging parameter of the thermal conductivity of thin insulating films.